Agrobiodiversity Index, tool to measure agrobiodiversity and identify concrete actions to achieve diverse and sustainable food systems - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
In early 2019, Bioversity International published the methodology and a separate report summarizing data from ten countries. Several public and private collaborations to apply the ABDI are ongoing, including with six companies that are including this in their corporate platforms.